2015
DOI: 10.1371/journal.pone.0138445
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Fruit Quality of Grapevines under Organic and Biodynamic Management

Abstract: The main objective of this study was to determine growth, yield and fruit quality of grapevines under organic and biodynamic management in relation to integrated viticultural practices. Furthermore, the mechanisms for the observed changes in growth, yield and fruit quality were investigated by determining nutrient status, physiological performance of the plants and disease incidence on bunches in three consecutive growing seasons. A field trial (Vitis vinifera L. cv. Riesling) was set up at Hochschule Geisenhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 54 publications
6
78
2
Order By: Relevance
“…In addition, Döring, et al (2015) observed similar yields in vines under biodynamic and organic farming; however, these cultivation methods showed lower values when compared to the integrated management. Scant information is available on the characteristics of biodynamic grapes and wine (Collins, et al, 2015;Parpinello, Rombolà, Simoni, & Versari, 2015;Plahuta & Raspor, 2007;Reeve, et al, 2005;Ross, Weller, Blue, & Reganold, 2009;Tassoni, Tango, & Ferri, 2013.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…In addition, Döring, et al (2015) observed similar yields in vines under biodynamic and organic farming; however, these cultivation methods showed lower values when compared to the integrated management. Scant information is available on the characteristics of biodynamic grapes and wine (Collins, et al, 2015;Parpinello, Rombolà, Simoni, & Versari, 2015;Plahuta & Raspor, 2007;Reeve, et al, 2005;Ross, Weller, Blue, & Reganold, 2009;Tassoni, Tango, & Ferri, 2013.…”
Section: Introductionmentioning
confidence: 81%
“…In the white cv. Riesling no differences on must soluble solids, pH and total acidity were detected among organic, biodynamic and integrated treatments, whereas α-amino-acids changed according to the cultivation method (Döring et al, 2015).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Despite these difficulties, a longitudinal study over 21 years that compared biodynamic, bioorganic, and conventional farming practices in Switzerland [6] reported enhanced soil fertility and increased biodiversity in their organic plots relative to the conventionally farmed plots. However, in a recent viticultural study [7], fruit quality was reported as not influenced by the organic and biodynamic management systems investigated. In terms of wine production, one of the few studies comparing biodynamic and organic viticulture that has been published in a peer-reviewed journal reported no consistent differences in any of the physical, chemical, and biological parameters measured [8].…”
Section: Introductionmentioning
confidence: 99%